EFFECT OF CAPITAL STRUCTURE, LEVERAGE, PROBITABILITY AND COMPANY SIZE ON FINANCIAL DISTRESS IN COMPANIES FOOD AND BEVERAGE MANUFACTURING - Yois Nelsari Malau; Angeline Theris; Jane Angelishan Salim; Wenny Anggeresia Ginting (Jurnal Ipteks Terapan, 2023)
The author conducted this research to understand the effect of capital structure, leverage, profitability and company size with financial distress through the Altman Z-Score model for food and beverage manufacturing companies listed on the IDX 2019-2021. This study uses secondary data and the sampling technique used is purposive sampling method in order to obtain 20 sample companies. The data will be analyzed using the binary logistic regression analysis test method with the SPSS 25 test tool. Based on the analysis conducted, the research results show that simultaneously the variables capital structure (DER), leverage (DAR), profitability (ROA) and company size have a significant impact on financial distress . While partially the variable capital structure (DER) and company size have a negative impact on financial distress . Leverage (DAR) and profitability (ROA) variables have a positive impact on financial distress